Effect of Temperature and Duration of Torrefaction on the Thermal Behavior of Stem Wood, Bark, and Stump of Spruce. (May 2017) - Barta-Rajnai, E.; Wang, L.; Sebestyén, Z.; Barta, Zs.; Khalil, R.; Skreiberg, Ø.; Grønli, M.; Jakab, E.; Czégény, Z.
Abstract: In this work the torrefaction of different parts of Norway spruce (stem wood, bark, and stump) was studied. Three different torrefaction temperatures were applied: 225, 275, and 300 °C with 30 and 60 minutes isothermal periods. The untreated and torrefied biomass materials were characterized by thermogravimetric analysis (TGA). The TGA results are interpreted in terms of the chemical composition determined by the cellulose, hemicellulose and Klason lignin content. The alkali ion contents of the samples were measured by ICP-OES technique. It was found that the effect of torrefaction temperature was greater than the effect of residence time up to 275 °C, while at 300 °C the residence time had a significant influence on the composition of the torrefied samples due to the intensive decomposition of cellulose.